1997
DOI: 10.1016/s0741-5214(97)70145-9
|View full text |Cite
|
Sign up to set email alerts
|

Duplex imaging findings predict stenosis after carotid endarterectomy

Abstract: Duplex scanning within a week of carotid endarterectomy identifies > 50% residual stenosis, in addition to minor residual 25% to 50% stenosis and small carotid dimensions, which are good predictors of > 50% restenosis at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Main findings ‫ء‬Vessel diameter Golledge et al 24 Preoperative, women generally had smaller carotid artery diameter than men. ‫ء‬Plaque morphology Hellings et al 25 Women have more stable and less inflammatory plaque phenotype compared with men.…”
Section: Influence Of Sex Hormonesmentioning
confidence: 97%
See 3 more Smart Citations
“…Main findings ‫ء‬Vessel diameter Golledge et al 24 Preoperative, women generally had smaller carotid artery diameter than men. ‫ء‬Plaque morphology Hellings et al 25 Women have more stable and less inflammatory plaque phenotype compared with men.…”
Section: Influence Of Sex Hormonesmentioning
confidence: 97%
“…This resulted in one additional article focusing on the difference in vessel diameter between men and women. 24 We wish to emphasize that this review did not aim to describe and summarize the actual outcome differences between men and women after CEA and all their theoretically related causes. We purposely focused our search on studies determining and specifying causal (gender-related) factors of the reported outcome difference.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that none of the above-mentioned studies analyze more than 1 factor simultaneously. [19][20][21][22][23][24][25][26][27][28][29] However, the overall evidence for outcome differences by gender-specific characteristics in the literature is limited. 30 Mantese et al found that sex did not modify the treatment effect.…”
Section: Discussionmentioning
confidence: 99%